2021
DOI: 10.1007/s11060-021-03744-4
|View full text |Cite
|
Sign up to set email alerts
|

MRI characteristics in treatment for cerebral melanoma metastasis using stereotactic radiosurgery and concomitant checkpoint inhibitors or targeted therapeutics

Abstract: Introduction Combination therapy for melanoma brain metastases (MM) using stereotactic radiosurgery (SRS) and immune checkpoint-inhibition (ICI) or targeted therapy (TT) is currently of high interest. In this collective, time evolution and incidence of imaging findings indicative of pseudoprogression is sparsely researched. We therefore investigated time-course of MRI characteristics in these patients. Methods Data were obtained retrospectively from 27 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…This desired synergistic effect might also lead to a higher rate of pseudoprogression. In metastasized melanoma to the brain, it was shown that a combination of radiotherapy and ICIs results in a higher rate of pseudoprogression than a combination of radiotherapy and targeted therapies ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…This desired synergistic effect might also lead to a higher rate of pseudoprogression. In metastasized melanoma to the brain, it was shown that a combination of radiotherapy and ICIs results in a higher rate of pseudoprogression than a combination of radiotherapy and targeted therapies ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…A combined therapy of ICIs and SRS appears beneficial [28], but is associated with an increase in pseudoprogression [29][30][31]. Also, ICI therapy of brain metastases may result in a greater occurrence of status epilepticus [32].…”
Section: Discussionmentioning
confidence: 99%